The effect of organizational factors and culture to organizational commitment in agency Financial Management, Income, and regional assets of Karo District - Evalina Veranita Br Bangun (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2021)
This research was conducted at the Agency Financial Management, Income and Regional Assets of Karo District with 41 employees as a sample which aims to determine: (1) significant influence of organizational on organizational commitments, (2) significant influence of organizational culture on organizational commitments and (3) influence organizational and organizational culture significantly to organizational commotments. The results showed that there was an influence of organizational on organizational commitments which was marked in the variable X1 with a value of tcount > ttable and there was also the influence of the organizational culture on organizational commitments marked in variable X2 with a value of tcount > ttable. The value of Fcount > Ftable shows that there is an influence of organizational and organizational culture on organizational commitments. The results of the calculation show that where rcount > rtable, all respondents' answers are valid. The Cronbach Alpha value is greater than 0.60, so the variable is reliable. In this study, there was no multicollinearity and heteroscedasticity neither. The multiple linear regression test is written in the regression equation Y=0,240+0,672X1+0,148X2. From the tests conducted, it was found that the samples were normally distributed. Based on the results of hypothesis testing, it was obtained that the value of tcount > ttable (6.600>2.022) for the organizational variable and (3,202>2.022) for the organizational culture variable; Fcount > Ftable (70,235>3,24); and the coefficient of determination obtained 80,7% while the remaining 19,3% is influenced by other variables outside of this study that must be considered in order to achieve better employee performance in the future. So Ha is accepted and Ho is rejected, so it can be concluded that there is an influence of motivation and work environment on employee performance.